Analysis Metacognition and Communication Mathematics in Blended Learning Use Google Classroom - Susilo, Joko; Kartono, Kartono; Mastur, Zaenuri (Unnes Journal of Mathematics Education Research, 2019)
Communication and metacognition ability of students in SMK N 11 Semarang is still low. Students have difficulties in presenting ideas with math language also their awareness of thinking is still low so that it difficult math problem solving .This study aims to know the effectiveness of blended learning use on communication and metacognition of students. The subject of the research is students class X AN 2 of SMK N 11 semarang 2018 / 2019 .The research uses qualitative and quantitative methods . Data is collected from filling out the questionnaires of metacognition and conducting metacognition ; also math communication test. The results show that ( 1 ) The awareness of metacognisi importance being masticated, students tend to be less optimal in using their experiences and knowledge to address the math issues . ( 2 ) Blended learning is significant on raising the awareness of metacognition .The majority of students having high metacognition because they tend to use their knowledge and experiences to finish math problems in high category . ( 3 ) Math communication ability of students on the linear equation system with two variables includes solved by average 80,1 .In terms of the indicators , the average of expressing math ideas (making math models) is 88,2 , the ability to count and understand is 79,2. Interpret and describe relations with math models or make inferences is 72;9.